Adaptive inter-piconet scheduling in small scatternets. - Mi?ić, Vojislav B. (Mobile computing and communications review.)
Inter-piconet scheduling in a Bluetooth scatternet may be performed in an adaptive manner, so as to minimize end-to-end packet delays. Using the theory of queues with vacations, we analyze the impact of different values of scatternet parameters on end-to-end delays, and then investigate the possibility of minimization of the aforementioned delays. We show that such minimization is possible for scatternets with both Slave/Slave and Master/Slave bridges, and that it should be based on inter-piconet traffic. We also describe simple algorithms that enable the scatternet to achieve near minimum delays in a wide range of traffic parameter values.